Imaging Tumor Heterogeneity and the Variations in Nanoparticle Accumulation Using Perfluorooctyl Bromide Nanocapsule X‐Ray Computed Tomography Contrast. Issue 8 (27th April 2022) - Beringhs, André O'Reilly; Ndaya, Dennis; Bosire, Reuben; Kasi, Rajeswari M.; Lu, Xiuling
Abstract: Systemically administered nanoparticles can extravasate into solid tumors through active or passive processes, showing high inter‐ and intraindividual variability, leading to inconsistent nanomedicine disposition in tumor lesions and variable therapeutic outcomes. Radio‐opaque Perfluorooctyl bromide‐loaded PEGylated cholesteryl‐functionalized polycaprolactone (PEG‐ b ‐PCL(Ch)) nanocapsules (PFOB NC) are assessed as imaging probes via X‐ray Computed Tomography (CT) as means to estimate nanoparticle disposition in solid tumors. This imaging platform can enable precision medicine by screening tumors for likelihood of nanoparticle accumulation prior to treatment. Single‐ and double‐lateral xenograft models are employed for imaging‐based nanoparticle accumulation assessment using a preclinical multimodal imaging system. Differences in tumor accumulation and spatial distribution are verified as a function of xenograft type via X‐ray CT and further corroborated by optical imaging. Slow growing OVCAR‐8 xenografts display granular distribution pattern and higher levels of PFOB NC disposition on a volume‐normalized basis. A549 xenografts, displaying faster growth, are less susceptible to PFOB NC accumulation and show only a diffuse‐like spatial distribution of the nanocapsule contrast. A direct correlation between tumor dispositions of PFOB NC and a commercial PEGylated liposomal doxorubicin formulation is found. This study highlights the potential of using nanoparticle‐based radio‐opaque contrasts to better understand nanoparticle disposition and foster improved therapeutic outcomes in cancer nanomedicine. Abstract : Perfluorooctyl bromide‐loaded PEG‐ b ‐PCL(Ch) nanocapsules extravasate into solid tumors upon intravenous administration. Real‐time kinetic extravasation of nanocapsules is precisely quantified via X‐ray Computed Tomography with optical imaging corroboration, providing critical insights on tumor characteristics and potential for nanoparticle disposition and deliverability prior to treatment.